Study of the Optical Properties for ZnS Thin Film Irradiated by CO2 Laser - Jassim, A. S.; Dahham, N. A.; Marie, M.Sh. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study ZnS thin film was prepared by using thermal evaporation vacuum technique under the pressure (10-6) Torr on glass substrate at room temperature and annealing at 523 K Samples were irradiated to CO2 laser of power (1 watt) and wave length (10.6) Î¼m at distance 10 cm from the source during (5 sec). The absorbance spectra was recorded by using UV-visible spectrophotometer and used to calculated some of optical properties investigated including their transmittance, reflectance spectra, energy gap, and extinction coefficient. From the result of thin films samples at room temperature and at 523 K, we conclude that the irradiation by laser causes a decrease in the transmittance and increasing in reflection and extinction coefficient and the irradiation leads to an increase in energy gap.